Voice Security Access Control for Home Door Lock and Appliances - Paiduthaly, Sathybabu; Hanafi, Dirman; M. Kwad, Ayad (Ijeepse, 2025)
Human voice and speech are among the most natural forms of communication, leading to extensive research into their application for security and access control. This paper presents a voice-based security access control system that leverages the HM2007 voice recognition IC and HM6264 (CMOS SRAM) to enable voice-commanded operation of doors using magnetic locks. Unlike traditional security mechanisms, such as key-based or biometric authentication (fingerprint and facial recognition), voice-based control offers a hands-free, non-contact alternative with increased accessibility. Experimental validation under quiet and noisy conditions demonstrates the system's robustness, with an accuracy of 86.67% in a quiet environment and 56.67% in a noisy setting. This study highlights the system’s ability to adapt to environmental conditions and mitigate common issues such as biometric spoofing and unauthorized access through stolen credentials.